2012
DOI: 10.1007/s00262-012-1226-4
|View full text |Cite
|
Sign up to set email alerts
|

Extended survival observed in adoptive activated T lymphocyte immunotherapy for advanced lung cancer: results of a multicenter historical cohort study

Abstract: PurposeTo clarify the long-term effect of immunotherapy, the effect of adoptive activated T lymphocyte immunotherapy on advanced lung cancer was evaluated in terms of survival time. In addition, the performance status of cancer patients under immunotherapy was examined.Experimental designOver 5 × 109 alpha–beta T lymphocytes cultured ex vivo with an immobilized anti-CD3 antibody and interleukin-2 were injected intravenously into patients, once every 2 weeks for 3 months or longer. Follow-up of these patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
3
23
0
1
Order By: Relevance
“…There is some evidence of an association between immunological ability and PS [7]. The present study showed a statistically significant association between change in the CD4/CD8 ratio before and after one course of adoptive immunotherapy and PS among different groups; the antecedent surgery group showed an important benefit of immunotherapy compared with the non-antecedent surgery group (p = 0.0179).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…There is some evidence of an association between immunological ability and PS [7]. The present study showed a statistically significant association between change in the CD4/CD8 ratio before and after one course of adoptive immunotherapy and PS among different groups; the antecedent surgery group showed an important benefit of immunotherapy compared with the non-antecedent surgery group (p = 0.0179).…”
Section: Discussionsupporting
confidence: 56%
“…Many physicians including Egawa, the founder of Japanese clinical immunotherapy who conducted the first clinical investigation of immunotherapy for cancer on his brother, have suggested that patients can maintain ordinary daily life activities during immunotherapy until close to the end of their life. To clarify this postulation, in the present study we analyzed PS during one course of adoptive activated immunotherapy [7,11,12]. Table 4…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jada abian dira immunoterapian oinarritzen diren saio kliniko batzuk, hesteetako hantura [3], gaixotasun autoimmuneak [4-6] edota minbizia [7,8] menderatzea helburu dutenak. Gaixotasunei aurre egiteko estrategia iraultzaile hau, duela hiru hamarkada sortu zen, melanoma pairatzen zuen gaixo bati T-zelulen hazkuntza bultzatzen duen 2-interleukina (IL-2) eman zitzaionean [9,10].…”
Section: Sarreraunclassified
“…The therapeutic efficacy of T-LAK therapy is thought to be mediated by the following 2 pathways: (1) cytotoxic activity of T-LAK against tumor cells (Sekine et al, 1993) and (2) activation of anti-tumor immune responses by various cytokines secreted from T-LAK (Kwak et al, 2000;Ishikawa et al, 2011). In human medicine, improvements in the proportions and cytokine production from autologous T lymphocytes have been reported (Hirokawa et al, 2009;Ishikawa et al, 2011;Sun et al, 2011;Noguchi et al, 2014) in addition to clinical effects, such as decreasing postoperative recurrence (Takayama et al, 2000;Xie et al, 2012;Zhong et al, 2012), improving quality of life Iwai et al, 2012), and prolonging survival Iwai et al, 2012;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 97%